Eksistensi pancasila dalam dinamika sejarah bangsa indonesia - Ishaqy, Aura Rihwa (Maliki Interdisciplinary Journal, 2026)
Pancasila is the foundation of the Indonesian state and ideology, born from the cultural values, customs, and worldview of the Indonesian people. Throughout the nation's history, Pancasila has undergone complex dynamics, both in its formulation and in its application during each period of government. This study aims to examine the existence of Pancasila in the historical dynamics of the Indonesian nation, starting from the pre-independence period, the Old Order era, to the Reformation era. The research method used is a literature study by compiling various scientific sources in the form of journals, books, and previous research results relevant to the topic of study. The results of the study show that Pancasila, as an open and democratic ideology, has always undergone a process of interpretation, reinforcement, and challenges in its implementation. During the Old Order era, Pancasila tended to be used as a tool to legitimize power through the concept of Guided Democracy. Meanwhile, in the Reformation era, Pancasila was reaffirmed as a national ideology relevant in facing the challenges of globalization, democratization, and moral and legal crises. Thus, Pancasila continues to play a strategic role as the foundation of the state, national ideology, and guideline for values in social, national, and state life.